Transmission spectra of InGaN single quantum wells and InGaN GaN heterostructures grown by metalorganic chemical vapor deposition - Kim, JW; Park, YK; Kim, YT; Son, CS; Choi, IH; Ambacher, O; Stutzmann, M (KOREAN PHYSICAL SOC, 1999)
The room temperature optical transmission spectra of GaN/InGaN/GaN single quantum wells and InGaN/GaN heterostructures grown by low-pressure metalorganic chemical-vapor deposition have been measured, The dependence of the absorption edge of the GaN/InGaN/GaN single quantum well on the well width has been determined from the transmission spectra. The result shows that the absorption edge of the GaN/InGaN/GaN single quantum well shifts towards lower energy as the well width increases. The dependence of the absorption edges of the InGaN/GaN heterostructures on the InN molar fraction has also been determined from the transmission spectra. The result is compared with Osamura's work, and in the range of a 0 - 0.1 InN molar fraction; our result shows better agreement with the calculated values of the bowing parameter; 1.05 eV, than Osamura's values do.
Keywords: TEMPERATURE-DEPENDENCE; OPTICAL-PROPERTIES; FILMS; CONSTANTS; DIODES